1992
DOI: 10.3177/jnsv.38.493
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory Nitrogen Losses in Pregnant Rats with Special Reference to Estimation of Net Protein Utilization.

Abstract: SummaryFor estimation of net protein utilization of dietary proteins during pregnancy, obligatory nitrogen losses were measured in protein deficient rats in which pregnancy was maintained by administration of ovarian steroids. On shift from normal to protein-free diet, urinary nitrogen, expressed as mg/day or mg/100g BW per day, decreased initially rapidly and then gradually during the first two weeks in both pregnant and nonpregnant rats. However, urinary endogenous nitrogen increased during the final week of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Previous reports (5,6), however, showed that pregnancy in rats fed PFD could be maintained with ovarian steroids, making it possible to estimate endogenous urinary and metabolic fecal nitrogen losses and to assess the NPUs of dietary proteins in pregnant rats (7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports (5,6), however, showed that pregnancy in rats fed PFD could be maintained with ovarian steroids, making it possible to estimate endogenous urinary and metabolic fecal nitrogen losses and to assess the NPUs of dietary proteins in pregnant rats (7).…”
Section: Discussionmentioning
confidence: 99%